2006
DOI: 10.1007/s00226-006-0107-4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Young’s and shear moduli of common yew and Norway spruce by means of ultrasonic waves

Abstract: Despite the exceptional position of yew among the gymnosperms concerning its elastomechanical properties, no reference values for its elastic constants apart from the longitudinal Young's modulus have been available from literature so far. Hence, this study's objective was to determine the Young's moduli E L , E R and E T and the shear moduli G LR , G LT and G RT of yew wood. For that purpose, we measured the ultrasound velocities of longitudinal and transversal waves applied to small cubic specimens and deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
58
2
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 18 publications
10
58
2
11
Order By: Relevance
“…Their research confirmed the fact that the higher the wood moisture, the lower the screw direct withdrawal load resistance. This dependence is also confirmed by Keunecke et al (2007) and Hübner et al (2010) who have identified the highest screw direct withdrawal load resistance in the radial plane (tangential direction) of wood. On the other hand, Ferah (1991) identified higher values of screw direct withdrawal load resistance in the radial direction in seven different wood types.…”
Section: Introductionsupporting
confidence: 74%
“…Their research confirmed the fact that the higher the wood moisture, the lower the screw direct withdrawal load resistance. This dependence is also confirmed by Keunecke et al (2007) and Hübner et al (2010) who have identified the highest screw direct withdrawal load resistance in the radial plane (tangential direction) of wood. On the other hand, Ferah (1991) identified higher values of screw direct withdrawal load resistance in the radial direction in seven different wood types.…”
Section: Introductionsupporting
confidence: 74%
“…When the parameters are derived from dynamic tests, the experimental parameters to be determined in the test pieces are the frequency (Yoshihara, 2012a) or the speed of the wavelength (Keunecke, Sonderegger, Pereteanu, Lüthi, & Niemz, 2007). The experimental results are pondered by the density of the wood, its temperature, the content of humidity at the moment of the test (Gorišek & Straže, 2013;Hernández, Passarini, & Koubaa, 2014) and by the anisotropy directions in which the test pieces were aligned (Brémaud et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the modulus of rigidity, some authors such as Naruse (2003); Keunecke et al (2007); Yoshihara (2012b); Ozyhar, Hering, Sanabria, and Niemz (2013); Kránitz, Deublein, and Niemz (2014) ;Nadir, Nagarajan, and Midhun (2014) and Sotomayor (2015) have reported data from several types of wood. The information on the modulus of elasticity determined through non-destructive methods and quality indexes of Mexican wood is lacking, with the exception of Sotomayor-Castellanos, GuridiGómez, and García-Moreno (2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fast measurements can be obtained by using different techniques based on ultrasonic (or acoustic) wave propagations in direct contact [3,4] or in a coupling medium (e.g., water) with a protective coating if dry wood properties have to be measured [5,6]. These techniques allow the determination of the diagonal terms of the elastic tensor on a unique parallelepipedic sample [7] but, except in some cases with a polyhedral [8] or spherical samples [6,9], they usually require other samples, and/or coupling with other kind of measurements, for the determination of off-diagonal terms [10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%